2018
DOI: 10.1177/1049731517753685
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Connecting People Intervention on Social Capital: A Pilot Study

Abstract: Objective: This pilot study evaluated the effect of the Connecting People Intervention (CPI) on access to social capital, social inclusion and mental well-being. Method: A prospective one group pretest-posttest pre-experimental study of 155 people with a mental health problem or a learning disability receiving care and support from health and social care practitioners trained in the CPI was used. Results: Participants exposed to practice with high fidelity to the CPI model had significantly higher access to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…The CPI articulates the process of a mental health worker assisting an individual to enhance their social network and engage more in their community. The CPI is centred on the partnership between a worker and an individual with mental health conditions, his/her family, and the surrounding community (Webber, Reidy, Ansari, Stevens, & Morris, 2016), and has shown to be effective in UK (Webber et al, 2018).…”
Section: Case Study 2: Connecting People In Sierra Leonementioning
confidence: 99%
See 1 more Smart Citation
“…The CPI articulates the process of a mental health worker assisting an individual to enhance their social network and engage more in their community. The CPI is centred on the partnership between a worker and an individual with mental health conditions, his/her family, and the surrounding community (Webber, Reidy, Ansari, Stevens, & Morris, 2016), and has shown to be effective in UK (Webber et al, 2018).…”
Section: Case Study 2: Connecting People In Sierra Leonementioning
confidence: 99%
“…Intervention research has shown that some of the burden of mental health conditions might be prevented by strengthening individuals, their friends and families, and the communities in which they live (Webber & Fendt-Newlin, 2017). There is some evidence, predominantly from high-income countries, that social interventions have the potential to improve quality of life (Webber, Huxley, & Harris, 2011), community engagement (Attree et al, 2011), social capital (Webber et al, 2018) and positively impact the social functioning (De Silva, Cooper, Li, Lund, & Patel, 2013) of people with mental health conditions. Central to shaping mental well-being and recovery from distress is the social environment in which an individual lives, but there is a lack of evidence around how to translate this link into effective and cost-effective interventions that enhance social outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research has demonstrated that those service users who develop their citizenship activities increase also their level of recovery [ 9 ]. This inter-relationships is not surprising, because being an active citizen enhances one’s personal and social identity, as well as enabling the acquisition of new skills and enriching one’s network [ 6 ]. At present, good correlations between these two variables are noted, rather than a clear causal relationships.…”
Section: Shared Decision Making Co-production and Active Citizensmentioning
confidence: 99%
“…As distinct from personal recovery, yet inter-related to it, social recovery includes the components of interdependence with others, connectedness [ 5 ], recovery capital [ 2 ] and social capital [ 6 ], as well as the impact of collective culture and the structural elements of our socio-economic-political system. To add to the complexity, the impact of each element on one’s identity, in interaction with how one is seen by others, needs to be taken into account.…”
Section: Introduction: What Is Social Recovery?mentioning
confidence: 99%
“…These outcomes are expected on the basis of findings of Connected Communities, Connecting People or similar initiatives to improve community engagement (e.g. Parsfield et al 2015;Webber et al 2019;O'Connor 2013).…”
Section: Contextmentioning
confidence: 97%